Special operations with respect to witness protection in the Czech Republic - Jacek Dworzecki (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The paper addresses the issue of special witness protection in the Czech Republic with respect to legal proceedings, organisational and tactical forms of protective actions implemented by the Police and the Prison Service towards persons admitted to protection programmes. The most significant legal acts regulating protective actions and operations adopted under the institution of an anonymous witness, special institution of witness protection and short-term protection have been drawn forward. Actions described in the paper constitute basic instruments of operational, exploratory and investigative work used by the Czech Republic Police in their fight against organised crime. The paper was written within the frame of a research project called “Understanding of Dimensions of Organized Crime and Terrorist Networks for Developing Effective and Efficient Security Solutions for First-line-practitioners and Professionals” (TAKEDOWN, H2020-FCT-2015, No: 700688).